Milk quality of properties with different technological standards Qualidade do leite de propriedades com diferentes padrões tecnológicos - Roza L.F.* (2015)
© 2015 Universidade Federal de Uberlandia. All rights reserved.This study aimed to assess the parameters of milk quality of properties with different technological standards. Twenty five properties were analyzed from 7 countries from the West of Santa Catarina, and classified according to production technologies (feeding, breeding and management practices in general), capital used in the activity, technological standard of machinery, equipment and infrastructure. Ten properties were classified as low technological standard, 8 intermediate standard and 7 high technological standard. The milk's quality data of each property (fat, protein, somatic cell count (SCC) and total bacterial count (TBC)) were supplied by dairy products, being used the average of the months of February, March and April of 2013. The data was subjected to multivariate statistical analysis and variance. It was found that the properties of low technological standard had higher fat content in milk, followed by intermediate and high standard which didn’t differ. The protein contents were higher in the properties of low standard with relation to intermediate standard, being that the high-tech standard didn't differ from the other groups. With regard to TBC, the properties of low-tech showed higher values when compared to the other groups, while the SCC did not differ between the different technological standards. We concluded that the technological standard of the properties influenced the parameters of protein, fat and TBC, being that in according with increased of the level of technological of properties, there was a decrease in these parameters, except that SCC didn’t show the same behavior, not being influenced by technological standards. The percentage variations in milk protein and fat were explained by racial pattern of the animals and the amount of concentrate supplied to the animals. The TBC was influenced by the milking hygiene practices, such as milking system’s pre-disinfection and the use of hot water in the sanitation of the equipment.